A CRISPR-Cas12a—Based platform for ultrasensitive, rapid, and highly specific detection of Mycoplasma pneumonia in clinical application - Jia, Nan; Zhou, Juan; Xiao, Fei; Zheng, Baoying; Huang, Xiaolan; Sun, Chunrong; Fu, Jin; Xu, Zheng; Chen, Min; Wang, Yi (Frontiers in Bioengineering and Biotechnology, 2023)
Mycoplasma pneumoniae (MP), which is responsible for a majority of community-acquired pneumonia (CAP) in children, has been largely underestimated. Here, we coupled multiple cross displacement amplification (MCDA) technique with CRISPR-Cas12a-based biosensing system to design a novel detection platform termed MP-MCDA-CRISPR assay for MP infection diagnosis and clinical application. The MP-MCDA-CRISPR assay amplified the CARDS gene of MP by MCDA method, followed by trans-cleavage of the reporter molecular upon the formation of CRISPR-Cas12a-gRNA-target DNA complex, which was confirmed by the release of fluorescent signals. A set of standard MCDA primers, an engineered CP1 primer, a quenched fluorescent ssDNA reporter, and a gRNA were designed targeting the CARDS gene of MP. The optimal temperature for MCDA pre-amplification is 64ºC, and the time for CRISPR-Cas12a-gRNA biosensing process is 5 minutes. The limit of detection (LoD) of the MP-MCDA-CRISPR assay is 50 fg per reaction without any cross-reaction with other non-MP pathogens. The MP-MCDA-CRISPR accurately identified the 50 real time-PCR positive clinical samples and 78 negative ones. Taken together, the MP-MCDA-CRISPR assay designed here is a promising diagnostic tool for POC testing of MP infection.